Correlation between previous sedentary lifestyle and CrossFit-related injuries - Paiva,Tiemi Maruyama de Moura (2021)
ABSTRACT: Objective: To correlate CrossFit-related injuries with previous sedentary lifestyle, and to investigate other factors potentially associated with higher rates of injury among practitioners. Methods: A nationwide cross-sectional study involving CrossFit practitioners who received a digital questionnaire inquiring into CrossFit-related injuries, previous sedentary life, training intensity and experience, site of injury and general demographics. Results: This sample included 121 CrossFit practitioners, 34.7% of participants were sedentary prior to starting CrossFit practice, from these, 45.2% reported CrossFit-related injuries, compared to 30.4% from previously active practitioners (p=0.104). The shoulder/elbow (60.5%), lumbar spine (30.3%) and wrist/hand (16.3%) were the most common sites of injury among participants reporting CrossFit-related injuries (35.5%). Participants performing intense weight training were more prone to injuries than those practicing light or moderate weight training (p=0.043). On average, participants with a history of injury spent significantly more time training than those with no history of injury (68.4 and 61.7 minutes, respectively; p=0.044). Conclusion: The incidence of CrossFit-related injuries did not differ significantly between previously sedentary and physically active participants. Intense weight training was associated with a higher incidence of injuries. The overall injury rate was 35.5%, similar to that found in previous studies, and the most common site of injury was shoulder/elbow.